PENGARUH CORPORATE GOVERNANCE PADA HUBUNGAN CORPORATE SOCIAL RESPONSIBILITY DAN NILAI PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Rara Saraswati; Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2013)
This study aims to investigate the influence of corporate governance and corporate social responsibility (CSR) on firm value of manufacturing companies listed on the Stock Exchange. Corporate governance is represented with managerial ownership, institutional ownership, independent commissary proportion, and the mamber of audit commitee as the moderating variabel. The sample is a manufacturing company listed on the Indonesia Stock Exchange on 2010-2011. The sample was selected using purposive sampling method and obtained a sample of 37 companies. Data analysis was performed with factor analysis, classical assumptions, and hypothesis testing with absolute value regression methode. The results show that corporate social responsibility has a significantly influence on firm value and corporate governance  as a moderating variable significantly influence on CSR and corporate value.